The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.rbmo.2021.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in PCOS characteristics and phenotype severity during a randomized controlled lifestyle intervention

Abstract: Research questionWhat is the effect of weight loss through different interventions (three-component lifestyle intervention with short message service (SMS+) vs three-component lifestyle intervention without SMS (SMS-) vs care as usual (CAU)) on PCOS characteristics (ovulatory dysfunction (OD), hyperandrogenism (HA), polycystic ovarian morphology (PCOM)) and phenotype distribution? DesignAnalysis of secondary outcome measures of a randomized controlled trial. Women (n=183) diagnosed with PCOS, a wish to become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…Although several studies have reported the importance of lifestyle management among patients with PCOS, 12 13 these studies did not clearly describe multidimensional life management with PCOS. Most studies focused on only one dimension of behaviour assessment, mainly nutritional intake and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although several studies have reported the importance of lifestyle management among patients with PCOS, 12 13 these studies did not clearly describe multidimensional life management with PCOS. Most studies focused on only one dimension of behaviour assessment, mainly nutritional intake and physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Weight [ 19 ], emotional well-being [ 24 ], phenotypical characteristics [ 25 ], and metabolic health [ 26 ] all were shown to improve more in the LSI groups compared to CAU over the course of our study. It is believed that the pre-pregnancy optimization of these factors should improve reproductive and obstetric outcomes in women with PCOS as well as in their offspring [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…The between groups weight loss differences did not translate into differences in ovulation dysfunction. A post‐hoc analysis showed that greater weight loss was associated with a lower chance of ovulation dysfunction 6 …”
Section: Lifestyle Behavioural Interventionsmentioning
confidence: 99%
“…A post-hoc analysis showed that greater weight loss was associated with a lower chance of ovulation dysfunction. 6 The potential importance of macronutrient composition in diet has been extensively studied and there is currently insufficient evidence to support a particular macronutrient dietary composition in women with PCOS for weight loss. 7 Very low energy diets (VLEDs) can lead to significant weight reductions of >15% after 12 weeks in women with PCOS.…”
Section: Lifestyle Behavioural Interventionsmentioning
confidence: 99%